Cameroon : Background Papers and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic and financial developments in Cameroon during the 1990s. Cameroon's economic and financial situation continued to deteriorate at a rapid pace in 1993/94. Real GDP growth was negative for the seventh year in a row, and the country's real per capita GDP declined by a cumulative 45 percent from the peak it had reached in 1985/86. Moreover, the external current account and fiscal deficits remained unsustainably large. With the devaluation of the CFA franc in early 1994, the environment for economic activity changed drastically.